Experimental optimization of aurocyanide adsorption onto biomass activated carbon and re-examination of the adsorption mechanisms - Bediako, J.K.; Affrifah, N.S.; Yun, Yeoung-Sang.; Repo, E. (Minerals Engineering, 2025)
Activated carbons (ACs) prepared from agricultural residues are ideal alternatives to the commercial coal-based ACs often applied in gold mining. Carbon activation using KOH produces high-quality carbons with good textural properties. Herein, fruit peel ACs were synthesized via KOH activation and evaluated for aurocyanide adsorption. The yield and adsorption capacity were optimized through a central composite design. The Langmuir maximum equilibrium uptake was 186.95 ± 16.44 mg/g. Re-examination of the adsorption mechanisms revealed that the presence of micro and mesopores, coupled with electrostatic binding, π–π interaction and ion-pair formations influenced the significantly high adsorption capacity. This study could be useful in the syntheses and application of agro waste-derived ACs as alternative adsorbents for gold recovery from aurocyanide leachates.
Research Article
Keywords: Biomass; KOH activation; Activated carbon; Aurocyanide; Mechanism; Ion pair